The Living-Related Kidney Transplant Program in Brunei Darussalam: Lessons Learnt from a Nascent National Program in a Small, Muslim, and Asian Country - Jackson Tan; Muhammad Abdul Mabood Khalil; Dalinatul Ahmed; Jayakrishnan Pisharam; Chiao Yuen Lim; Hock Beng Chua; William Chong; Kim Khee Tan (Journal of Transplantation)
Brunei Darussalam commenced its living-related renal transplant program in 2013, with subsequent attainment of independent local capacity and proficiency in 2019. The preliminary outcome from the program has already begun to shape the national nephrology landscape with a 36% increment in transplant rate and mitigation of commercialized transplantations. The blueprint for the program was first laid out in 2010 and thereupon executed in four phases. The first phase involved the gathering of evidence to support the establishment of the national program, through researches investigating feasibility, public opinion, quality of life, graft survival, and cost-effectiveness. The second phase focused on laying the foundation of the program through grooming of local expertise, implementation of legal-ethical frameworks, religious legitimization, and propagation of awareness. The third phase worked on facilitating experiential exposure and strengthening local infrastructure through the upgrading of facilities and the introduction of subsidiary services. The fourth phase was implemented in Brunei in 2013 when foreign personnel worked together with the local team to perform the transplants. Between 2013 and 2019, ten kidney transplants were performed, with two being done in 2018 and three in 2019. We hope to inspire other similar countries to develop their own self-sustainable and independent local program.